(untitled) (Journal of Global Accounting, 2023)
This study examined how dividend policy and its interaction with capital investment affects share price volatility in Nigeria banking industry from 2013-2022. The study used a sample of 13 commercial banks quoted on the Nigeria stock exchange Preliminary analyses were also conducted, such as descriptive statistics and correlation matrix. In analyzing the data, the study adopted panel multiple regression to identify the possible effects of dividend policy and capital investment on share price volatility. The study employed Pooled and panel data regression with least square dummy variable as time and organizational dummies were created to account for any effect which vary over time and across section. The result showed that dividend per share and dividend pay-out ratio has a significant positive effect on share price volatility while dividend yield shows a significant negative effect on share price volatility while earnings volatility is insignificant. However the interaction of dividend yield and capital investment (dy*capinv) indicates a 5% significant negative influence on share price volatility this implies that in every 5% reduction in dividend yield and capital investment there will be a 5% reduction in share price. We concluded that corporate managers of the banks quoted on the Nigerian stock exchange can use dividend policy as a tool to control/manage share price volatility. We therefore, recommends that banks should try and improve on their financial performance that will enable consistent increase in the dividend per share for positive impact on market value.